Surgical and Prosthetic Rehabilitation of Combination Syndrome. (6th January 2014) - Carlino, Paolo; Pettini, Francesco; Cantore, Stefania; Ballini, Andrea; Grassi, Felice Roberto; Pepe, Valentina
Abstract : The aim of this report is to analyze the clinical symptoms, ethologic factors, and prosthetic rehabilitation in a case of Combination Syndrome (CS). The treatment of CS can be conventional or surgical, with or without the bone reconstruction of maxilla. The correct prosthetic treatment helps this kind of patients to restore the physiologic occlusion plane to allow a correct masticatory and aesthetic function. Management of this kind of patients can be a challenge for a dental practitioner.